IMPLEMENTASI METODE TILAWATI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN PADA MAHASISWA NON-PESANTREN DI STIT DARUL ULUM KOTABARU - Haiqal Rahman; Muhammad Nafis Asshidqi; Latifah Zakiah; Laila Nur Dzakiroh; Tari Siska Anggelia; Mirna Wati (STIT DARUL ULUM KOTABARU, 2026)
This research is motivated by the persistent problems of Al-Qur'an reading ability among non-Islamic boarding school students, particularly regarding the fluency of makhraj, understanding of tajwid, and self-confidence. STIT Darul Ulum Kotabaru, as the first Islamic college in Kotabaru, faces challenges in improving the Al-Qur'an reading competence of students with general education backgrounds. The Tilawati method offers a solution with its distinctive characteristics of using Rost tones and a classical-individual approach. The formulation of the problem includes: (1) the Al-Qur'an reading ability of non-Islamic boarding school students before and after the implementation of the Tilawati method; (2) the implementation of the Tilawati method in improving makhraj fluency and tajwid understanding; (3) the supporting and inhibiting factors in its implementation. The research aims to describe these three aspects holistically. This research uses a qualitative approach with a case study type. The research location is at STIT Darul Ulum Kotabaru, involving 6th-semester students. Research subjects were determined using purposive sampling, including the lecturer in charge of the Tilawati Al-Qur'an course and 36 non-Islamic boarding school students. Data collection techniques used participatory observation, in-depth interviews, and documentation. The main instrument was the researcher themselves, supported by semi-structured interview guides, observation sheets, and document checklists. Data analysis used the Miles and Huberman interactive model (data condensation, data display, conclusion drawing). Data validity was ensured through credibility, transferability, dependability, and confirmability. The results showed that before the implementation of the Tilawati method, non-Islamic boarding school students experienced difficulties in makharijul huruf, tajwid rules, reading fluency, and learning motivation. After participating in the learning, there was a significant improvement of up to 70% in fluency, tajwid accuracy, and makhraj clarity. The use of Rost tones proved effective as a quality control tool for classical reading while helping to internalize tajwid rules naturally. The learning stages of classical, read-listen, and individual ensured each student received personal correction. Supporting factors include lecturer patience, student internal motivation, and a supportive classroom atmosphere. Inhibiting factors include difficulty following tones, differences in initial abilities, time constraints, and feelings of insecurity. In conclusion, the Tilawati method is highly effective in improving the Al-Qur'an reading ability of non-Islamic boarding school students at STIT Darul Ulum Kotabaru.